2023
DOI: 10.1086/721735
|View full text |Cite
|
Sign up to set email alerts
|

What Do Employee Referral Programs Do? Measuring the Direct and Overall Effects of a Management Practice

Abstract: Employee referral programs (ERPs) are randomly introduced in a grocery chain. Larger referral bonuses increase referrals and decrease referral quality, though the increase in referrals from having an ERP is modest. However, the overall effect of having an ERP is substantial, reducing attrition by roughly 15% and decreasing firm labor costs by up to almost 3%. This occurs, partly, because referrals stay longer than nonreferrals, but, mainly, because all workers stay longer in treated than control stores, even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…We have shown that having a supportive leader is essential for a healthy workplace climate. Reducing the job separation rate is particularly valuable in times of tight labor markets, (Friebel et al, 2023), and here the leader's support plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that having a supportive leader is essential for a healthy workplace climate. Reducing the job separation rate is particularly valuable in times of tight labor markets, (Friebel et al, 2023), and here the leader's support plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that having a supportive leader is essential for a healthy workplace climate. Reducing the job separation rate is particularly valuable in times of tight labor markets, (Friebel et al, 2023), and here the leader's support plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, companies have increasingly recognized that employees and alumni are effective company ambassadors and are seen as having authentic opinions about the company's culture, working atmosphere, career development opportunities, and work experience (Arief et al, 2022;Smith et al, 2021). Positive employee advocacy and word-of-mouth referrals have been shown to reduce recruitment costs, increase the company's employer branding reach, attract prospective employees with values similar to the companies, and increase the company's credibility (Dechawatanapaisal, 2020;Friebel et al, 2023). Therefore, companies should encourage their existing employees to share job vacancies, sustainability practices, and other positive company activities on their personal social media.…”
Section: Earned Digital Mediamentioning
confidence: 99%